The effect of using exercises with educational methods according to Culp style in order to retain some basic handball skills - Salih, Asst .Prof. Dr. Mateen Sulaiman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem of research is through the researcher's observation that some methods of implementation of the lesson depend on the teacher's academic experience and may not fit perhaps with the abilities of the learner or the student when studying the game handball and practicing it with sufficient time and mastering the skills of the game, which makes the student a recipient and a beneficiary of the teacher's orders and not provide sufficient opportunities to develop his skill level, which called for the need to use educational exercises in the method of learning cooperative in order to master that may contribute to raising the level of performance and improving the learning curve and retaining some basic skills with handball. The research aims to influence the use of educational exercises in the method of cooperative learning in order to be able to learn some basic skills in handball and keep them for students of the Faculty of Physical Education and Sports Sciences / Kirkuk University,, and the researcher used the experimental method to suit the nature and problem of research, while the research community included students of the Faculty of Physical Education and Sports Sciences / Kirkuk University for the academic year 2019/2020 while the sample of research was made up of 30 students They randomly divided the experimental and controlled groups and by (15) students per group ,and the researcher conducted exploratory experiments and identified the skills in and tribal tests and applied the method of educational exercises and dimensional tests and the use of statistical bag Spss to extract the results of the research and through this the researcher concluded that the educational exercises in the method of cooperative learning in order to be able positively in learning some basic skills with handball and retaining.